Investigation on Wearable Antenna under Different Bending Conditions for Wireless Body Area Network (WBAN) Applications - Ismahayati Adam; Muhammad Ramlee Kamarudin; Ali H. Rambe; Norshakila Haris; Hasliza A. Rahim; Wan Zuki A. Wan Muhamad; Arif M. Ismail; Muzammil Jusoh; Mohd Najib M. Yasin (International Journal of Antennas and Propagation)
This paper analysed the effects of bending on the performance of a textile antenna wherein the antenna under test was made of felt substrate for both industrial, scientific, and medical (ISM) band and WBAN applications at 2.45 GHz. Moreover, the conductive material was used for the patch, and the ground plane used a 0.17 mm Shieldit textile. Meanwhile, the antenna structure was in the form of rectangular, with a line patch in between elements to abate the mutual coupling effect. The measured operating frequency range of the antenna spanned from 2.33 GHz to 2.5 GHz with a gain of 4.7 dBi at 2.45 GHz. In this paper, the antenna robustness was examined by bending the structure on different radii and degrees along both X- and Y-axis. Next, the effects on return loss, bandwidth, isolation, and radiation characteristics were analysed. This paper also discovered that the antenna’s performance remained acceptable as it was deformed, and the measured results agreed well with the simulation.